Predictors of achievement in college algebra - Monta, Florentina Daquila (Animo Repository, 1997)
The study focused on the best predictors of achievement in College Algebra using 333 freshmen students of the Central Luzon State University (CLSU). The criterion (dependent) variable was the achievement in College Algebra and the independent variables were student, parent, and school factors. The study was conducted for a period of one full semester (1st semester, SY 96-97), covering the whole syllabus of College Algebra in CLSU. Results showed that among selected student factors, attitude towards mathematics, College Admission Test (CAT) mathematics subscore, fourth year high school average grade and fourth year high school mathematics grade had significant and positive correlation with students' mathematics achievement. On the other hand, none of the parent factors was found to be correlated with students' mathematics achievement. However, among school factors, only the type of school curriculum had significant correlation with students' mathematics achievement. The best predictors of achievement in College Algebra were CAT mathematics performance and attitude towards mathematics.